Pengaturan Cuti Notaris dalam Keadaan Mendesak yang Hanya Dapat Dilakukan Keluarga Sedarah Garis Lurus Notaris - Ayuni, Prianggieta; Subawa, Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Abstract :  The purpose of this research is to provide knowledge and to study and analyze problems regarding notary leave arrangements in urgent situations which can only be carried out by the Notary's blood line family. This research uses normative legal research. Notary leave arrangements in urgent situations are determined in Article 28 UUJN, however there are multiple interpretations or unclear norms in the phrase "urgent circumstances: in the formulation of Article 28." So, based on these regulations, an urgent situation in Article 28 UUJN, if using a systematic interpretation, can be interpreted as an urgent situation if the Notary does not have the opportunity to apply for leave due to carrying out education and training, courses, work visits outside the region/country, illness, leave, fulfilling Hajj / Umrah or other similar reasons. The notary's responsibility if the notary's leave in an urgent situation cannot be fulfilled because he or she does not have a spouse or family member who is of the same blood line is administrative responsibility. If a Notary is in an urgent situation and does not have a husband/wife or blood family in a direct line to the Notary himself or even has blood relatives but is not legally competent to take legal action, then the Notary will not be able to submit a leave request to the Regional Supervisory Council. Notaries who do not apply for leave will be deemed not to have carried out their obligations in accordance with UUJN orders as stipulated in Article 27 jo. Article 28 UUJN, Notaries who wish to take leave must apply for leave. If the Notary violates the obligations and prohibitions of the position as well as the Notary's code of ethics, this can cause the Notary to be temporarily suspended as stipulated in Article 9 UUJN.   Abstrak : Tujuan penelitian ini adalah guna memberikan pengetahuan dan guna mengkaji serta menganalisa permasalahan mengenai pengajuan permohonan cuti kepada Majelis Pengawas Daerah oleh Notaris dalam keadaan mendesak. Metode yang digunakan adalah metode penelitian normatif. Pengaturan cuti bagi Notaris di Indonesia di atur pada UUJN. Setiap Notaris memiliki hak untuk cuti, hak Cuti sebagaimana yang telah disebutkan dalam Pasal 25 UUJN. dapat diambil setelah Notaris menjalankan jabatanya selama 2 (dua) tahun. selama menjalankan cuti Notaris wajib mengusulkan Notaris pengganti. Kemudian, Pasal 26 menentukan  selama menjalankan jabatanya, Notaris berhak mengambil cuti, yang dapat diambil setelah menjalankan tugas jabatanya selama 2 (dua) tahun. Jumlah keseluruhan cuti diambil Notaris tidak lebih dari 12 (dua belas) tahun. Sesuai dengan karakter jabatan Notaris yaitu harus berkesinambungan selama Notaris masih dalam masa jabatanya, maka Notaris yang bersangkutan wajib menunjuk Notaris pengganti. Kriteria keadaan mendesak dalam pengaturan hak cuti bagi seorang Notaris yakni terdapat pada pasal 28 UUJN menyebutkan bahwa dalam keadaan mendesak, suami/istri atau garis lurus dari Notaris dapat mengajukan permohonan Cuti kepada Majelis Pengawas. Penjelasan keadaan mendesak disini bahwa apabila seorang Notaris tidak mempunyai kesempatan untuk mengajukan permohonan cuti karena berhalangan sementara, berhalangan sementara apabila dilihat dalam UUJN tidak dijelaskan secara rinci bahkan dalam aturan pelaksanaanya juga tidak menjelaskan terkait dengan keadaan mendesak ini.